Simultaneous series and shunt earth fault detection and classification using the Clarke transform for power transmission systems under different fault scenarios - Esmail, Ehab M.; Alsaif, Faisal; Abdel Aleem, Shady H. E.; Abdelaziz, Almoataz Y.; Yadav, Anamika; El-Shahat, Adel (Frontiers in Energy Research, 2023)
For high-voltage (symmetric and non-symmetric) transmission networks, detecting simultaneous faults utilizing a single-end-based scheme is complex. In this regard, this paper suggests novel schemes for detecting simultaneous faults. The proposed schemes comprise two different stages: fault detection and identification and fault classification. The first proposed scheme needs communication links among both ends (sending and receiving) to detect and identify the fault. This communication link between both ends is used to send and receive three-phase current magnitudes for sending and receiving ends in the proposed fault detection (PFD) unit at both ends. The second proposed scheme starts with proposed fault classification (PFC) units at both ends. The proposed classification technique applies the Clarke transform on local current signals to classify the open conductor and simultaneous faults. The sign of all current Clarke components is the primary key for distinguishing between all types of simultaneous low-impedance and high-impedance faults. The fault detection time of the proposed schemes reaches 20 ms. The alternative transient program (ATP) package simulates a 500 kV–150-mile transmission line. The simulation studies are carried out to assess the suggested fault detection and identification and fault classification scheme performance under various OCFs and simultaneous earth faults in un-transposed and transposed TLs. The behavior of the proposed schemes is tested and validated by considering different fault scenarios with varying locations of fault, inception angles, fault resistance, and noise. A comparative study of the proposed schemes and other techniques is presented. Furthermore, the proposed schemes are extended to another transmission line, such as the 400 kV–144 km line. The obtained results demonstrated the effectiveness and reliability of the proposed scheme in correctly detecting simultaneous faults, low-impedance faults, and high-impedance faults.